THE EFFECTIVENESS OF GROUP COUNSELING THROUGH THE GESTALT APPROACH IN INCREASING INTROVERT PERSONALITY CONFIDENCE - Sari Harahap; Netrawati (Yayasan Citra Dharma Cindekia, 2021)
Starting from the background that some people do not realize that low self-confidence can cause a person to be unable to self-actualize. Self-confidence is an attitude or feeling of confidence in one's own abilities that can develop self-awareness, think positively, have independence, and have the ability to have and achieve something desired. This study aims to see the effectiveness of the implementation of group counseling through the gestalt approach. The research is aimed at people who have introverted personalities. This research uses literature study. Where library research is a study that is used to collect information and data with the help of various materials in the library such as documents, books, magazines, historical stories. The data collection technique used is library research, namely by looking for data about things or variables in the form of notes, books, papers or journal articles, where the instrument used in this case is a check-list. The results in this study are group counseling services can increase self-confidence through a gestalt approach. The gestal approach is very effective so that a person's self-confidence can increase.